COST-EFFECTIVENESS ANALYSIS OF HERPES ZOSTER VACCINATION IN ITALIAN ELDERLY PERSONS. (14th September 2016) - Coretti, Silvia; Codella, Paola; Romano, Federica; Ruggeri, Matteo; Cicchetti, Americo
Abstract : Objectives: Herpes zoster (HZ) is characterized by a painful skin rash. Its main complication is postherpetic neuralgia (PHN), pain persisting or occurring after the rash onset. HZ treatment aims to reduce acute pain, impede the onset complications, and disease progression. The aim of this study was to assess the cost-effectiveness of HZ vaccination compared with no vaccination strategy, within the Italian context. Methods: The natural history of HZ and PHN was mapped through a Markov model with lifetime horizon. A population of patients aged between 60 and 79 years was hypothesized. Third party payer (Italian National Health Service, I-NHS) and societal perspectives were adopted. Data were derived from literature. Results and Conclusions: The incremental cost-effectiveness ratio of the vaccination equaled EUR 11, 943 per quality-adjusted life-year (QALY) under the I-NHS perspective and EUR 11, 248 per QALY under the societal perspective. Considering a cost-effectiveness threshold of EUR 30, 000/QALY, the multi-way sensitivity analysis showed that vaccination is cost-effective regardless of the perspective adopted, in 99 percent of simulations.